2015
DOI: 10.30537/sijmb.v2i1.88
|View full text |Cite
|
Sign up to set email alerts
|

What Determines Balance of Payments: A Case of Pakistan

Abstract: Distortion in balance of payments is one of the dominant causes for the sluggish economic condition of Pakistan. The present article has focused to scrutinize the relationship of the balance of payments to its certain determinants that are actually blamable or not for its distortion. The robust ARDL structure has been utilized to develop the bound testing approach to co-integration and error correction models on data set for 1972-2013.The bound test declares that there exists stable long run relationship of ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The study also presented recommendations towards the achievement of growth in the market-segment to improve exports and creating employment, in addition to regulating inflation to reduce poverty and reducing imports of non-productive goods. In another study, Batool et al (2015) determined the BoP in Pakistan using data for the period between 1972 and 2013. Here the findings from the study revealed that a steady long-run association prevailed regarding the BoP and its causes.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The study also presented recommendations towards the achievement of growth in the market-segment to improve exports and creating employment, in addition to regulating inflation to reduce poverty and reducing imports of non-productive goods. In another study, Batool et al (2015) determined the BoP in Pakistan using data for the period between 1972 and 2013. Here the findings from the study revealed that a steady long-run association prevailed regarding the BoP and its causes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The first variable, Money Supply is described as the amount of currency that people and banking departments of SBP hold, deposits with SBP, net foreign assets of SBP, and scheduled bank demand deposits, etc., which are incorporated with respect to the meaning of money supply as mentioned by (Batool et al, 2015). The second variable is the interest rate (R), which is the sum charged represented as a percentage to the primary amount, by a lender (the creditor) to a borrower (the debtor) utilized as assets.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation